Nuptial flight in ants (Hymenoptera: Formicidae) - Stukalyuk, Stanislav; Akhmedov, Ascar; Stelia, Valery; Shymanskyi, Artem; Netsvetov, Maksym (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2022)
Based on the collected data set (758 observations for the period 2007-2021) on the dates of the nuptial flight for 73 species of ants, an analysis of possible time shifts due to global climate changes has been carried out. It was found that for Eastern Europe and Asia, for most species of ants, the dates of nuptial flight were shifted by at least two weeks earlier in comparison with the data for Western Europe. In a cold climate, there are significant changes, towards earlier dates, in the phenology of nuptial flight for two species: Lasius flavus (P<0.05) and Polyergus rufescens (P<0.01). The corresponding rates of change are 3.9 and 6.25 days per year. In other types of climate, no significant changes in the phenology of the nuptial flight were found. Taking into account the boundaries of future climatic zones in temperate and arid zones, such changes were recorded for several species. Solenopsis fugax in temperate climates shows a tendency to delay flight at a rate of 6 days per year (P<0.05). Within the predicted boundaries of the arid climate, the flight phenology delay was recorded for Lasius niger (5.8 days per year; P<0.01) and Messor sp. (4.4 days per year; P<0.05). At the same time, for Polyergus rufescens, there is a tendency to an earlier flight at a rate of eight days per year (P<0.05). No connection was found between the date of nuptial flight and the geographic distance between populations (or locations).